Weeds. Season four [videorecording (DVD)] - Kohan, Jenji, 1969- (Lions Gate Entertainment, 2009)
Last time we saw her, Nancy's business and house were going up in smoke. So the Botwin bunch has relocated near the border for a fresh start with some new buds.